The lost : a search for six of six million - Mendelsohn, Daniel Adam 1960- (HarperCollins, 2006)
For five years, Daniel Mendelsohn traveled the globe searching for an answer to the question he had first asked as a boy decades earlier: What really happened to his great-uncle's family during the Holocaust? Here, Mendelsohn weaves together his discoveries about the past, family secrets and Judaism itself. He visits nearly a dozen countries on four continents in pursuit of the truth, eventually interviewing the town's twelve living survivors. Along the way, he detects things that challenge family myths and inspire new questions about long-held beliefs. Interwoven throughout the present-day developments are flashbacks to Mendelsohn's youth spent with his immigrant relatives, and more generally to Jewish life, philosophy and tradition over the years. Not only does he come to know his six deceased relatives on this unforgettable journey, but he discovers so much more about himself, his religion, his immediate family and their shared history as well.--From publisher description.